Clusterin Induces MUC5AC Expression via Activation of NF-κB in Human Airway Epithelial Cells - Bae, Chang Hoon; Choi, Yoon Seok; Song, Si-Youn; Kim, Yong-Dae (Clinical and experimental otorhinolaryngology, 2018)
Clusterin (CLU) is known as apolipoprotein J, and has three isoforms with different biological functions. CLU is associated with various diseases such as Alzheimer disease, atherosclerosis, and some malignancies. Recent studies report an association of CLU with inflammation and immune response in inflammatory airway diseases. However, the effect of CLU on mucin secretion of airway epithelial cells has not yet been understood. Therefore, the effect and brief signaling pathway of CLU on MUC5AC (as a major secreted mucin) expression were investigated in human airway epithelial cells. In the tissues of nasal polyp and normal inferior turbinate, the presence of MUC5AC and CLU was investigated using immunohistochemical stain and Western blot analysis. In mucin-producing human NCI-H292 airway epithelial cells and primary cultures of normal nasal epithelial cells, the effect and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathway of CLU on MUC5AC expression were investigated using immunohistochemical stain, reverse transcription-polymerase chain reaction, real-time polymerase chain reaction, enzyme immunoassay, and Western blot analysis. In the nasal polyps, MUC5AC and CLU were abundantly present in the epithelium on immunohistochemical stain, and nuclear CLU (nCLU) was strongly detected on Western blot analysis. In human NCI-H292 airway epithelial cells or the primary cultures of normal nasal epithelial cells, recombinant nCLU increased MUC5AC expression, and significantly activated phosphorylation of NF-κB. And BAY 11-7085 (a specific NF-κB inhibitor) and knockdown of NF-κB by NF-κB siRNA (small interfering RNA) significantly attenuated recombinant nCLU-induced MUC5AC expression. These results suggest that nCLU induces MUC5AC expression via the activation of NF-κB signaling pathway in human airway epithelial cells.